2017
DOI: 10.1186/s40168-017-0241-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural variability and niche differentiation in the rhizosphere and endosphere bacterial microbiome of field-grown poplar trees

Abstract: BackgroundThe plant microbiome represents one of the key determinants of plant health and productivity by providing a plethora of functional capacities such as access to low-abundance nutrients, suppression of phytopathogens, and resistance to biotic and/or abiotic stressors. However, a robust understanding of the structural composition of the bacterial microbiome present in different plant microenvironments and especially the relationship between below-ground and above-ground communities has remained elusive.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
290
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(370 citation statements)
references
References 116 publications
54
290
1
2
Order By: Relevance
“…Mexican Dioon species, similar to that detected in the root endosphere from angiosperm plants as Arabidopsis [27], sugarcane [46], poplar trees [47], and inside the specialized root nodules of legumes [48]. We found that Proteobacteria, Actinobacteria, Cyanobacteria, Bacteroidetes and Planctomycetes were the dominant bacterial phyla in the Dioon coralloid root microbiome.…”
Section: A Taxonomically Diverse Bacterial Community Inside Dioon Corsupporting
confidence: 77%
“…Mexican Dioon species, similar to that detected in the root endosphere from angiosperm plants as Arabidopsis [27], sugarcane [46], poplar trees [47], and inside the specialized root nodules of legumes [48]. We found that Proteobacteria, Actinobacteria, Cyanobacteria, Bacteroidetes and Planctomycetes were the dominant bacterial phyla in the Dioon coralloid root microbiome.…”
Section: A Taxonomically Diverse Bacterial Community Inside Dioon Corsupporting
confidence: 77%
“…In addition to the higher alpha diversity (richness and evenness) found in the olive rhizosphere microbial communities compared to that observed for the microbiota inhabiting the root endosphere, and the finding that quite different communities were found in each compartment, a common scenario described in several studies 25,26 , the following major results must be highlighted from our work. Concerning the endosphere, cultivars originating from Syria showed the highest diversity level in contrast to the Turkish cultivars that showed the lowest one.…”
Section: Discussionsupporting
confidence: 60%
“…Unidentifiable sequences or sequences classified as Eukaryota , chloroplasts, mitochondria, or Wolbachia (endosymbiont) were removed. Low abundance sequences (singletons, doubletons, and tripletons) could potentially reflect the rare biosphere of a microbial community (D Ainsworth et al., ), but to avoid inflating the actual microbial diversity in the cricket gut due to PCR or sequencing errors (Dickie, ; Kunin, Engelbrektson, Ochman, & Hugenholtz, ), singletons were excluded from downstream analyses (Beckers, Op De Beeck, Weyens, Boerjan, & Vangronsveld, ; Tedersoo et al., ) (quality control step 7). Finally, a total of nineteen OTUs, with a maximum of three sequence reads for any individual OTU, were obtained from all the negative controls.…”
Section: Methodsmentioning
confidence: 99%